2015
DOI: 10.1182/blood-2014-12-616565
|View full text |Cite
|
Sign up to set email alerts
|

Sample conditions determine the ability of thrombin generation parameters to identify bleeding phenotype in FXI deficiency

Abstract: Key Points• When contact activation is inhibited, Factor XI:C levels only correlate with thrombin generation if platelets are present.• Thrombin generation measured in platelet-rich plasma with contact activation inhibition identifies bleeding phenotype in FXI deficiency.Individuals with Factor XI (FXI) deficiency have a variable bleeding tendency that does not correlate with FXI:C levels or genotype. Comparing a range of sample conditions, we tested whether the thrombin generation assay (TGA) could discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 31 publications
4
51
0
1
Order By: Relevance
“…Last, the TGA is reportedly suitable for detecting an AT deficiency and seems less influenced by FXI. TGA is more sensitive to FXI in the presence of platelets and when the tissue factor concentration is low . In our conditions, when TGA is assessed in platelet‐poor plasma with high tissue factor concentration (5 pmol/L), the thrombin generation profile is primarily driven by antithrombin deficiency.…”
Section: Discussionmentioning
confidence: 87%
“…Last, the TGA is reportedly suitable for detecting an AT deficiency and seems less influenced by FXI. TGA is more sensitive to FXI in the presence of platelets and when the tissue factor concentration is low . In our conditions, when TGA is assessed in platelet‐poor plasma with high tissue factor concentration (5 pmol/L), the thrombin generation profile is primarily driven by antithrombin deficiency.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, a recent study demonstrated that a thrombin generation assay in platelet-rich plasma (PRP) in which the contact pathway was inhibited while the extrinsic pathway was activated via TF was able to successfully identify which FXI-deficient patients demonstrated a bleeding phenotype [16]. These differing results suggest that FXI does not play a role hemostasis via the contact pathway but that FXI can initiate coagulation via the extrinsic pathway in the presence of TF and platelets.…”
Section: Fxi and Hemostasismentioning
confidence: 99%
“…Curiously, this discriminatory ability was lost if TF or CTI was added, indicating fXIa generated by fXIIa was being measured. In contrast, Pike et al noted significant differences in thrombin generation between fXI deficient bleeders and non-bleeders in platelet-rich plasma with 0.5 pM TF and CTI, [48]. Here, the inclusion of platelets may have provided a co-factor for fXI activation by thrombin in the form of polyphosphate [2729].…”
Section: Introductionmentioning
confidence: 99%